Steroids from Hedyotis leptoneura - Dien, Pham Huu; Trang, Do Thuy; Hai Yen, Lam Thi; Quang, Dang Ngoc (Vietnam Journal of Chemistry, 2015)
Four metabolites, 7β,19α-dihydroxy-3β-isoarborinol, 3β-isoarborinol, stigmasta-5,22-diene-3β-ol and daucosterol, were isolated from the aerial parts of Hedyotis leptoneura plant, collected in Bach Ma National Park (Thua Thien – Hue Province). Their structures were elucidated by various spectroscopic analyses.